RENIN-ALDOSTERONE RATIO: AN AUDIT ON SAMPLES AND RESULTS IN HOSPITAL TELUK INTAN - Sun, Choon Peng; Saleh, Nursyahirah; Shari, Syazana Jan (Journal of the ASEAN Federation of Endocrine Societies, 2025)
INTRODUCTION Primary aldosteronism (PA) is an important yet often under-diagnosed cause of secondary hypertension. The renin-aldosterone ratio (RAR) serves as a key screening test for PA. This audit evaluates the number of RAR samples sent, their outcomes, and their implications for clinical practice over a three-year period from 2022 to 2024. As RAR testing is not available in Hospital Teluk Intan, all samples must be outsourced to Hospital Putrajaya, with an average turnaround time of approximately one month. The objective of this audit is to determine the number of RAR tests performed in Hospital Teluk Intan. Additionally, it seeks to analyze the proportion of positive and negative results and assess the adequacy of PA screening among hypertensive patients. METHODOLOGY This retrospective audit was conducted over a three-year period from January 2022 to December 2024. The study included all patients tested for RAR in Hospital Teluk Intan, while cases with incomplete results or missing data were excluded. Data was collected from laboratory records and patient files. RESULT Over the study period, a total of 48 RAR tests were conducted. In 2022, two cases tested positive while 18 were negative. In 2023, two cases were positive and 11 were negative. In 2024, one case was positive and 14 were negative. Among the five patients with positive results, two underwent adrenalectomy and subsequently recovered. Two patients declined further treatment due to advanced age and concerns about worsening kidney disease, while one patient remains under investigation. CONCLUSION Although a significant number of RAR tests were performed, the majority yielded negative results, reinforcing the fact that primary aldosteronism remains a relatively rare condition compared to primary hypertension. The audit findings suggest that approximately one in ten tested cases were diagnosed with PA. These results highlight the importance of targeted screening to ensure appropriate patient selection for RAR testing, thereby optimizing resource utilization and timely intervention.